The Impact of Exchange Rate Changes on Indonesian Exports - Denny Saputera; John Henry Wijaya; Rizqi Muttaqin (International Journal of Economics (IJEC), 2023)
This study delves into how Exchange Rates and Gross Domestic Product (GDP) have shaped Indonesian exports over the past 17 years, from 2006 to 2022. On the whole, Indonesian exports have generally shown a positive trajectory during this period, although there have been occasional drops in specific years. The main countries that receive Indonesian exports are China, the United States, Japan, India, and Malaysia, and the primary export goods include coffee, animal and vegetable fats and oils, Crude Palm Oil (CPO), and coal. When we look at long-term model analyses, it becomes evident that exchange rates play a significant role in negatively affecting Indonesian exports. This means that, over an extended period, an increase in the value of the Indonesian currency can lead to a reduction in export volumes. Furthermore, GDP also exerts a notable negative influence on Indonesian exports, suggesting that the overall economic growth of the country can impact export levels. In the context of short-term model estimations, it is apparent that fluctuations in currency exchange rates have a substantial negative impact on Indonesian exports in the immediate term, assuming all other factors remain constant. The results of these estimations also indicate that GDP has a considerable negative effect on Indonesian export performance in the short run.